Robust environmental DNA assay development and validation: A case study with two vulnerable Australian fish. Issue 7 (3rd April 2022) - Wilkes Walburn, Jackson; Rourke, Meaghan L.; Furlan, Elise; DiBattista, Joseph D.; Broadhurst, Matt K.; Fowler, Ashley M.; Hughes, Julian M.; Fielder, Stewart
Abstract: Analysis of environmental (e)DNA can facilitate an understanding of the presence and distribution of aquatic species. However, eDNA detection using quantitative PCR requires validated and standardized species‐specific assay designs. This study presents two eDNA assays to detect Murray cod, Maccullochella peelii, and mulloway, Argyrosomus japonicus (two ecologically vulnerable Australian species), based on small fragments of the mitochondrial 12S ribosomal RNA gene. A comprehensive description of species‐specific assay development, from assay design to testing in silico, in vitro and in situ, has been included to guide effective assay design and validation in future studies. The results indicate that the assay was species specific for M. peelii within its natural distribution. However, the assay also amplified genomic DNA from two allopatric and endangered congeners ( Maccullochella ikei and Maccullochella mariensis ), thus potentially facilitating their eDNA detection elsewhere. In contrast, the A. japonicus assay was highly species specific with no amplification among close relatives. Both target‐species assays are highly sensitive to as few as four and 10 copies per PCR reaction, respectively. This study has demonstrated that the assays assessed are effective tools for detecting the targeted species in situ from environmental DNA samples, which will assist efforts to conserve and manage their stocks.